2018
DOI: 10.1186/s12882-018-1133-9
|View full text |Cite
|
Sign up to set email alerts
|

An IgA1-lambda-type monoclonal immunoglobulin deposition disease associated with membranous features in a patient with IgG4-related kidney disease: a case report

Abstract: BackgroundIgG4-related disease (IgG4-RD) is a newly recognized fibroinflammatory condition. The kidney is one of the organs commonly affected by IgG4-RD. Tubulointerstitial nephritis (TIN) is the main feature, and membranous nephropathy (MN) has also been described frequently. In MN, polyclonal immunoglobulins and complements are deposited in granular form along the glomerular basement membranes (GBMs). Unusual cases of monoclonal immunoglobulin deposition disease (MIDD) associated with membranous features hav… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 28 publications
0
12
0
Order By: Relevance
“…There are several case reports of monoclonal IgA-type MN or IgA-type MIDD with membranous features [3, 4, 5]. Sethi [3] reported an MN patient with IgA-κ deposits and crescents.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…There are several case reports of monoclonal IgA-type MN or IgA-type MIDD with membranous features [3, 4, 5]. Sethi [3] reported an MN patient with IgA-κ deposits and crescents.…”
Section: Discussionmentioning
confidence: 99%
“…In this case, the relationship between chronic hepatitis C viral infection and monoclonal gammopathy was considered. Kitazawa et al [5] reported a case of IgA1-λ-type MIDD associated with membranous features. This case also had IgG4-related tubulointerstitial nephritis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For primary glomerulopathies such as MN [131,189,190], IgA nephropathy [191,192,193,194], or FSGS [195,196,197], an association with PBE was mainly found when described in the context of primary eosinophilia-associated diseases like Kimura’s disease, EGPA, IgG4-RKD, or HES.…”
Section: Eosinophilia In Kidney Diseasementioning
confidence: 99%
“…Hyperproteinemia is a metabolic disease, which has recently been reported to be associated with an abnormally elevated plasma protein concentration (PPC) as a clinical symptom [1][2][3][4][5]. This hyperproteinemia is commonly exhibited in many important clinical diseases in humans, as well as other mammals (e.g., multiple myeloma [4,6], nephropathy [7][8][9][10], hepatopathy [11,12], and pathogen infections [2,13]). Hyperproteinemia also appears in metabolic acidosis and even clinical plasma therapy or intravenous immunoglobulin therapy [9,[14][15][16].…”
Section: Introductionmentioning
confidence: 99%